Clinical significance of serum cystatin C‐to‐creatinine ratio as a surrogate marker for incident osteoporotic fracture predictions - Ichiro Yoshii; Naoya Sawada; Tatsumi Chijiwa (Journal of General and Family Medicine)
Abstract Background Detection of appropriate indicators is valuable for preventing incidental osteoporotic fractures. We statistically evaluated the significance of serum cystatin C‐to‐creatinine ratio (CysC/Cr) as a surrogate marker for incident major osteoporotic fractures (MOF) prediction. Methods Eligible patients with simultaneous measurement of CysC/Cr and bone mineral density in the lumbar spine and proximal femur were selected, and their fracture histories until 5 years after baseline were observed in the retrospective area cohort data. Patients who were followed up until termination or the first osteoporotic fracture were included, and loss of follow‐up or death was excluded. Candidate risk factors for osteoporotic fractures were tested for risk ratios using a cox regression analysis. Receiver operating characteristic tests were performed on factors with significantly higher risk ratios and evaluated with Kaplan‐Meier survival analysis to determine the hazard ratios of the factors. Results A total of 175 patients of whom 28 had incident MOF, 38 men, and 137 women, were enrolled. The mean age was 70.2 years. A significantly higher risk ratio was shown in the presence of prevalent MOF, hyper fall‐ability, lifestyle‐related diseases, chronic kidney diseases ≥ Grade3a, and higher CysC/Cr. All parameters had cutoff indices and showed significantly higher hazard ratios. Conclusions These results suggested that CysC/Cr may be a predictive marker of incident osteoporotic fractures. It might work as a screening tool for MOF risk.